Students' Attitudes and challenges towards Pecha Kucha Presentation Technique in Teaching English Introduction Online - Awaluddin - Syamsu (LEAD (Language, Education and Development), 2022)
Recent decades Pecha Kucha has gained its acknowledgement as one of the language teaching tools. This research aimed at finding out the tertiary students’ attitude towards the use of Pecha Kucha in English introduction lessons and identifying difficulties that were experienced by the students in the process of making and presenting their Pecha Kucha. Survey method with two types of questions, multiple choices and open ended questions, were employed. The result of the study indicated that students had positive attitude to use Pecha Kucha in English introduction lessons because they believe that Pecha Kucha can facilitate their learning and also they enjoyed the making and presenting their Pecha Kucha. Students experience different challenges in the making and presentation process of their Pecha Kucha. The making process students highlight 5 challenges, finding pictures, gadgets, narration, English, and presentation skills, whereas there are 6 challenges students encounter during their presentation time, English skills, unstable connection, self-confidence, time constrain of Pecha Kucha, memorizing their presentation, and internet data. The different challenges in the making and presentation of PK are justifiable due to the unique nature of the two processes.